Rapid weight gain following weight cutting in male and female professional mixed martial artists - Murugappan, K. R.; Mueller, A.; Walsh, D. P.; Shaefi, S.; Leibowitz, A.; Sarge, T. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
Rapid weight loss or "weight cutting" is a common but potentially harmful practice used in mixed martial arts competition. Following the official weigh-in, competitors refeed and rehydrate themselves in a process known as rapid weight gain (RWG) to realize a potential competitive advantage. While data from surveys and small series have indicated the majority of mixed martial arts athletes engage in rapid weight loss, there is a lack of officially collected data from sanctioning organizations describing its prevalence. The present investigation represents a summary of the data collected between December 2015 and January 2018 by the California State Athletic Commission. In total, 512 professional mixed martial artists (455 males and 57 females) were included. Of these, 503 (98%) athletes gained body mass between weigh-in and their bouts. Total RWG between weigh-in and competition was 5.5 ± 2.5 kg, corresponding to an 8.1% ± 3.6% body mass increase. Total RWG was 5.6 ± 2.5 kg (8.1% ± 3.6%) for males and 4.5 ± 2.3 kg (8.0% ± 3.8%) for females. More than one quarter of men and one third of women gained >10% body mass between weigh-in and competition. Athletes from leading international promotions gained more absolute, but not relative, body mass than those from regional promotions. Our findings indicate RWG is nearly ubiquitous in professional , with a similar prevalence in male and female athletes. Trends based on promotion suggest a larger magnitude of RWG in presumably more experienced and/or successful mixed martial artists from leading international promotions.